2023
DOI: 10.3390/children10020240
|View full text |Cite
|
Sign up to set email alerts
|

Playing at the Schoolyard: “The Who’s, the What’s and the How Long’s” of Loose Parts

Abstract: Play has a key role in children psychomotor development, and the quality of play spaces can be a facilitator of the former. The physical properties of the environment, such as equipment or material available, can influence children’s behavior. However, it is not clear how the provision of different loose parts impacts children’s play patterns. This study aimed to analyze the influence of four types of loose parts on the time, frequency and number of children using them during free play sessions. We recorded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The loose parts provided opportunities for unstructured play that could be active or sedentary, depending on how children decided to use the materials and space. The type of loose parts available can shape children’s play decisions and experiences [ 16 ]. The play hubs aimed to encourage child-led unstructured play rather than specifically promoting physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loose parts provided opportunities for unstructured play that could be active or sedentary, depending on how children decided to use the materials and space. The type of loose parts available can shape children’s play decisions and experiences [ 16 ]. The play hubs aimed to encourage child-led unstructured play rather than specifically promoting physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effectiveness of LLP interventions on physical activity and play tend to be implemented within early education settings (e.g., childcare centres, preschools and elementary schools) [ 6 , 15 , 16 , 17 , 18 ]. However, studies investigating LLP interventions delivered to the public in community outdoor settings are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Mereka dapat belajar melalui permainan, eksplorasi, dan kolaborasi dengan teman sebaya. Faktor ini membantu meningkatkan motivasi dan minat anak-anak terhadap pembelajaran (Pereira et al, 2023). Penggunaan media loose part juga melibatkan interaksi langsung dengan bahan-bahan dan objek-objek nyata, yang memungkinkan anakanak untuk membangun pemahaman secara konkrit.…”
Section: B Pembahasanunclassified
“…Researchers and educators became aware that the tendency to reduce the involvement of children in free play and outdoor time compromises children's psychosocial and motor development [17]. In this Special Issue, the space outside the classroom was also addressed, either by focusing on play-based intervention in the outdoors [18] by examining play behaviors of children deaf and hard of hearing (DHH) in the outdoor school playground [19] or by developing a sensor-based instrument to analyze children's behaviors and its relationship with the playground affordances. Specifically, Pereira et al [18] analyses of children's play patterns during ten play sessions in a primary school showed that all four types of materials (tarpaulin/fabrics, cardboard boxes, plastic crates, and plastic tubes) have the same importance for these children.…”
mentioning
confidence: 99%
“…In this Special Issue, the space outside the classroom was also addressed, either by focusing on play-based intervention in the outdoors [18] by examining play behaviors of children deaf and hard of hearing (DHH) in the outdoor school playground [19] or by developing a sensor-based instrument to analyze children's behaviors and its relationship with the playground affordances. Specifically, Pereira et al [18] analyses of children's play patterns during ten play sessions in a primary school showed that all four types of materials (tarpaulin/fabrics, cardboard boxes, plastic crates, and plastic tubes) have the same importance for these children. Moreover, Silva et al [19] showed that DHHs do not play as much as their hearing peers and that interventions are needed to transform the physical environment into a more friendly and socially facilitating context.…”
mentioning
confidence: 99%